2021
DOI: 10.1002/ejic.202100256
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Bismuth Complexes with Benzoazacrown Tri‐ and Tetra‐Acetates

Abstract: The complexation properties towards Bi 3 + of benzoazacrown ligands with five (H 3 BA3A) and six (H 4 BATA) heteroatoms and corresponding number of acetic arms have been investigated. Complexation constants were determined via potentiometric titration for BA3ABi complex (logβ = 26.2) and refined for BATABi complex (logβ = 31.7). According to NMR, X-ray and EXAFS results, chelation of cation by H 3 BA3A appears to be outside the macrocyclic cavity both in the solid state and in the aqueous solution. This out-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…The more precise kinetic study presented in this work (see below) also demonstrated the high rate of complex formation, even under acidic conditions and at room temperature. This made it possible to determine the stability constant of the H 4 BATA complex with Bi 3+ by standard potentiometric titration in a chloride medium to prevent the hydrolysis of Bi 3+ [36] . The stability constants of the forms of the H 4 BATA complex with Bi 3+ obtained here were very high, which made it difficult to accurately determine them.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The more precise kinetic study presented in this work (see below) also demonstrated the high rate of complex formation, even under acidic conditions and at room temperature. This made it possible to determine the stability constant of the H 4 BATA complex with Bi 3+ by standard potentiometric titration in a chloride medium to prevent the hydrolysis of Bi 3+ [36] . The stability constants of the forms of the H 4 BATA complex with Bi 3+ obtained here were very high, which made it difficult to accurately determine them.…”
Section: Resultsmentioning
confidence: 93%
“…That fact was confirmed by the high in vivo stability of the complex. [36] In summary, the H 4 BATA ligand is suitable for application as a component of bismuth-based radiopharmaceuticals.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier we have developed a series of azacrown ethers with an aryl substituent in the macrocycle. It was shown that 15-azacrown-5 and 18-azacrown-6 with acetate pendant arms, are appropriate for various medically relevant radiometals [ 4 , 5 , 7 , 8 ], but are inappropriate for Cu 2+ . Additionally, the complete substitution of acetate by pyridyl induced a decrease in the water-solubility of the ligands [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the growing importance of nuclear medicine and the extending abilities of obtaining medically relevant radiometals, the design of functional polyazamacrocyclic ligands able to coordinate cations with suitable features has been attracting increased attention during the last decade. In the frame of systematic variation and the search for the best matching pairs between medical radiometals and chelators, we have synthesized those substituted with one type of arm and arm-free pyridine bisamide azacrown and benzoazacrown ethers [ 1 , 2 , 3 , 4 , 5 , 6 ]. We have shown that azacrown compounds with acetic arms are effective for binding bismuth [ 4 , 5 ], lead [ 7 ] and zinc [ 8 ] cations, regarding the nuclear medicine application of their radioisotopes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation